Combined intra-extra-articular technique for stabilisation of coxofemoral luxation - Venturini, A.; Pinna, S.; Tamburro, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2010)
Objective: To report a new technique for repairing traumatic cranio-dorsal coxofemoral luxation in dogs.Methods: Stabilisation of hip luxation was carried out in two dogs: a one-year-old male Border Collie and an eight-year-old female American Staffordshire Bull Terrier. A caudal approach was performed to expose the hip joint. Following this, a 2.5 mm hole was drilled through the acetabular wall at the original attachment of the round ligament, followed by a tunnel between the fovea capitis and the proximal third of the femur. Nylon tape was tied in a clove hitch knot around the femoral neck. The tape was placed as a bridge over the ischial spine to create an acetabular roof in order to increase articular stabilisation. Results: Follow-up examinations were performed at 10, 40 and 90 days after surgery.The dogs did not show any signs of lameness, pain or reoccurrence of the luxation during any of the follow-up examinations.Clinical significance: This tape-technique enabled reinforcement of the acetabular roof which in turn increased the stability of the joint.
Keywords: Coxofemoral luxation; clove hitch; Bühner tape; dog